Persistence of Seed Dispersal in Agroecosystems: Effects of Landscape Modification and Intensive Soil Management Practices in Avian Frugivores, Frugivory and Seed Deposition in Olive Croplands - Rey, Pedro J.; Camacho, Francisco M.; Tarifa, Rubén; Martínez-Núñez, Carlos; Salido, Teresa; Pérez, Antonio J.; García, Daniel (Frontiers in Ecology and Evolution, 2021)
Farming impacts on animal-mediated seed dispersal through mechanisms operating at least at two spatial scales: first, at the landscape scale, through habitat loss and land conversion to agriculture/livestock grazing, and second, by local intensification (farm scale) of the agricultural practices. Nonetheless, these two scales of farming impact on the seed dispersal function have been rarely integrated. In particular, studies evaluating the effect of agriculture in the seed dispersal function of frugivorous birds in Mediterranean ecosystems are lacking. We evaluate the role of the landscape transformation, from fruit-rich woodland habitats to olive grove landscapes, together with the local intensive practices of soil management on the persistence of the seed dispersal function for Mediterranean fleshy-fruited plants in olive landscapes of south Spain. We used bird censuses, mist-nets and seed traps to characterize avian frugivore assemblages, frugivory, and seed deposition in seminatural woodland habitat (SNWH) patches and olive fields of 40 olives farms of 20 localities distributed across the whole range of olive cultivation in Andalusia (southern Spain). We found that despite of a still remarkable dispersal function in olive grove landscapes, avian frugivore abundance and diversity, frugivory, and seed arrival decreased in olive fields compared to SNWH patches. Likewise, SNWH cover loss and/or olive growing expansion decreased avian frugivory and seed arrival. Interestingly, habitat effects in the olive farms often depended on the landscape context. In particular, less diverse fruit-eating bird assemblages pooled in SNWH patches as olive grove cover increased or SNWH decreased in the landscape, while remained relatively invariant in the olive fields. Finally, compared to conventional intensive agriculture, low-intensity management increased frugivory and seed deposition. We conclude that olive fields are less permeable to frugivores than expected by its agroforest-like nature, and that presence of SNWH patches is crucial for the maintenance of frugivory and seed dispersal in agricultural landscapes. Results evidence that woodland habitat loss by olive expansion and the intensive practices seriously threaten the dispersal service in olive-dominated landscapes. Maintenance, restoration and promotion of woodland patches should be prioritized for the conservation of the seed dispersal service and for enhancing the functional connectivity in human-shaped olive landscapes.